2020
DOI: 10.1002/jmv.26227
|View full text |Cite
|
Sign up to set email alerts
|

Impaired glucose metabolism in patients with diabetes, prediabetes, and obesity is associated with severe COVID‐19

Abstract: Background Identification of risk factors of severe Covid‐19 is critical for improving therapies and understanding SARS‐CoV‐2 pathogenesis. Methods We analyzed 184 patients hospitalized for Covid‐19 in Livingston, New Jersey for clinical characteristics associated with severe disease. Results The majority of Covid‐19 patients had diabetes mellitus (DM) (62.0%), Pre‐DM (23.9%) with elevated FBG, or a BMI > 30 with normal HbA1C (4.3%). SARS‐CoV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
128
3
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(152 citation statements)
references
References 22 publications
13
128
3
8
Order By: Relevance
“…Finally, prediabetes, characterized by elevated fasting blood glucose or impaired insulin sensitivity, has been mostly overlooked in COVID-19 studies, but could nevertheless pose a threat to clinical outcomes (Box 1). In a US study of 184 patients, most had diabetes (62.0%) or prediabetes (23.9%), and stratifying patients solely by elevated fasting blood glucose or HbA1c increased the risk of intubation (35). A China study also found that elevated fasting blood glucose (>7.54 mmol cut-off) independently predicted mortality (HR 1.19) (26).…”
Section: Glycemic Control and Elevated Fasting Blood Glucosementioning
confidence: 99%
“…Finally, prediabetes, characterized by elevated fasting blood glucose or impaired insulin sensitivity, has been mostly overlooked in COVID-19 studies, but could nevertheless pose a threat to clinical outcomes (Box 1). In a US study of 184 patients, most had diabetes (62.0%) or prediabetes (23.9%), and stratifying patients solely by elevated fasting blood glucose or HbA1c increased the risk of intubation (35). A China study also found that elevated fasting blood glucose (>7.54 mmol cut-off) independently predicted mortality (HR 1.19) (26).…”
Section: Glycemic Control and Elevated Fasting Blood Glucosementioning
confidence: 99%
“…19,20 Uncontrolled hyperglycemia has been linked to increased morbidity and worse outcomes in recent studies. 21 Severe COVID-19 infection may result in significant hyperglycemia not only in those with pre-existing diabetes but also in patients who have prediabetes, obesity or no previous risk factors. This is due to multiple mechanisms: increased secretion of counter-regulatory hormones, increased inflammatory response, medications such as glucocorticoids, inotropes and dextrose-containing fluids, inadequate and unpredictable oral intake, and a direct effect of SARS-CoV-2 on pancreatic islets.…”
Section: Management Of Hyperglycemia In Covid-19 Infected Patientsmentioning
confidence: 99%
“…This is due to multiple mechanisms: increased secretion of counter-regulatory hormones, increased inflammatory response, medications such as glucocorticoids, inotropes and dextrose-containing fluids, inadequate and unpredictable oral intake, and a direct effect of SARS-CoV-2 on pancreatic islets. 21 The management of hyperglycemia in infected individuals follows the general principles of hyperglycemia management during acute illness. [22][23][24] Regular point-of-care blood glucose monitoring is recommended in all sick patients including those with pre-existing diabetes.…”
Section: Management Of Hyperglycemia In Covid-19 Infected Patientsmentioning
confidence: 99%
“…The initial search yielded 1177 articles, of which 636 were deduplicated and 482 were excluded following title and abstracts screening, resulting in the retrieval of 59 records for full-text assessments-among which 13 Table S4). In quantitative analysis, 10 studies were excluded as seven [18][19][20][21][22][23][24] only reported P-value and three [25][26][27] reported different effect measures.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…From 35 included studies, more than half were conducted in China (23 studies), while the others were five each in America 18,21,[27][28][29] and Europe 20,25,[30][31][32] , and one each in Hong Kong 33 and South Korea 34 . FBG was utilized in 23 studies, while RBG in 13 studies.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%